2012
DOI: 10.1037/a0028423
|View full text |Cite
|
Sign up to set email alerts
|

A latent profile analysis of Asian American men's and women's adherence to cultural values.

Abstract: The goal of this study was to identify diverse profiles of Asian American women's and men's adherence to values that are salient in Asian cultures (i.e., conformity to norms, family recognition through achievement, emotional self-control, collectivism, and humility). To this end, the authors conducted a latent profile analysis using the 5 subscales of the Asian American Values Scale-Multidimensional in a sample of 214 Asian Americans. The analysis uncovered a four-cluster solution. In general, Clusters 1 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…In the labor market, wage discrimination against Asian-American men has ended [29] . Culturally, Asian Americans, particularly Asian-American men, are driven by the cultural norm of high educational achievement [30] , [31] . Psychologically, stereotype lift enhances Asian performance in domains where Asians are positively stereotyped [32] , [33] .…”
Section: Introductionmentioning
confidence: 99%
“…In the labor market, wage discrimination against Asian-American men has ended [29] . Culturally, Asian Americans, particularly Asian-American men, are driven by the cultural norm of high educational achievement [30] , [31] . Psychologically, stereotype lift enhances Asian performance in domains where Asians are positively stereotyped [32] , [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Generalizing from these findings to other ethnic groups therefore may not accurately capture associations between masculinity and health outcomes, and may also possibly misrepresent a variety of factors that shape the expression of masculinity for men of color (Griffith et al, 2012; Liu, 2002; Schwing, Wong, & Fann, 2013; Wong, Owen, Tran, Collins, & Higgins, 2012). That is, although many men of color in the United States may adhere to mainstream masculine norms, there is reason to believe that ethnic minority men may also draw upon other aspects of masculinity to form their own standards and definitions of what it is to be masculine (Abreu, Good-year, Campos, & Newcomb, 2000; Griffith et al, 2012; Liu, Iwamoto, & Chae, 2010; Wong, Owen, et al, 2012). …”
mentioning
confidence: 99%
“…Several scholars (Lee, 1996; Liu, Iwamoto, & Chae, 2010; Wong, Nguyen, et al, 2012) have noted that different socialization upbringings and standards of masculinity are propagated in Asian cultures; this varying socialization process creates a different mind-set for Asian American men relative to White American men. Chua and Fujino’s (1999) study found greater cultural variability in what was considered masculine in U.S.-born and immigrant Asian men relative to White American men.…”
mentioning
confidence: 99%
“…For instance, Asian international students who strongly adhere to emotional selfcontrol and humility may be negatively viewed by their American peers and professors as unassertive, unapproachable, or emotionless, which may in turn result in an increased sense of alienation and despair. In line with these notions, a recent latent profile analysis of Asian Americans' adherence to Asian values identified a cluster of relatively depressed participants, which included high levels of adherence to emotional self-control and humility (Wong et al, 2012).…”
Section: Application Of a Person × Context Frameworkmentioning
confidence: 90%
“…Although several dimensions of Asian values (e.g., conformity to norms) conflict with dominant European American values, adherence to emotional self-control and humility may inflict the greatest psychological cost for Asian international students living in the United States. Because these values emphasize self-effacement, they directly conflict with the dominant European American values of assertiveness and expressiveness (Sue & Zane, 2009;Wong et al, 2012). For instance, Asian international students who strongly adhere to emotional selfcontrol and humility may be negatively viewed by their American peers and professors as unassertive, unapproachable, or emotionless, which may in turn result in an increased sense of alienation and despair.…”
Section: Application Of a Person × Context Frameworkmentioning
confidence: 99%